The Effect of Food Diet Training on the Quality of Life among Non-Dialysis Patients with Chronic Renal Disease - M Pourshaban; Z Parsayekta; M Gholamnezhad; H Haghani; N Karimi (Iran University of Medical Sciences, 2013)
Abstract   Background & Aim: Chronic renal disease is highly associated with reduced quality of life and nurses are responsible for promotion of the quality of life of these patients and lead them to a balanced life by appropriate interventions. This study was aimed to determine the effect of food diet training on the quality of life of non-dialysis patients with chronic renal disease.   Material & Methods: It was a quasi-experimental before-after nonequivalent comparative group study. Eighty chronic renal disease patients with Glomerular Filtration Rate of 15-60 ml/min/1.73 m2, were recruited and assigned by purposive sampling either to control or experimental groups (n=40). The experimental group received food diet training package and the control group received only usual care. Before and after 12 weeks, patients were evaluated by Kidney Disease Quality of Life _ iranian_Final_ver1.3 questionnaire. The data were analyzed by descriptive and inferential statistics (t-test and chi square) using SPSS-PC(v.16).   Results : After 12 weeks significant differences were found in the physical and mental components of the general dimension and overall quality of life between the two groups(P <0.05). There were also significant differences in the specific dimension of quality of life including signs and symptoms, effects of disease, limitations associated with illness, satisfaction and total health between the two groups(P <0.05).   Discussion and Conclusion: Increasing the awareness of non - dialysis chronic renal disease patients using this method would improve their quality of life.   Received: 4 March 2013   Accepted: 2 Jun 2013